Consumer Perspectives on Chemical-Free Food Purchase: Identifying Determinant Factors - Rana, Bishal (Devkota Journal of Interdisciplinary Studies, 2023)
In response to heightened consumer concern regarding long-term health and a trend towards health-beneficial purchases, this study seeks to scrutinize the influential factors dictating Chemical-free food purchase intentions in Butwal, Sub-Metropolitan City. The primary objective of this research is to examine the impact of health consciousness, knowledge, and trust on an individual’s inclination to buy Chemical-free food. Using a randomly distributed self-administered questionnaire, data from 200 respondents were analyzed. The analysis, conducted through Pearson Correlation and Multiple Regression, aimed to discern the relationships and impacts of the various factors on the inclination to purchase organic products. This study found that knowledge was the most important factor that significantly increased people’s intentions to buy organic foods. This was in contrast to trust and health consciousness, which had no discernible effect on people’s buying habits. Given these findings, the paper suggests that enhanced government and policy interventions are necessary to foster organic farming and stimulate consumer awareness, thereby facilitating an increase in Chemical-free food purchases.